A Case of Early Hereditary Transthyretin Amyloid Cardiomyopathy Recognition With Genetic Screening: A Case Report - Michel Juarez; Gaspar Del Rio-Pertuz; Kanak Parmar; Melanie C. Bois; Scott Shurmur; Erwin Argueta-Sosa (SAGE Publishing, 2022)
Background: Transthyretin amyloid cardiomyopathy (ATTR-CM) is one of the most common types of cardiac amyloidosis. Amyloid cardiomyopathy more commonly affects men, elderly, and 3% to 4% of the African-American population. ATTR-CM suspicion and diagnosis is challenging; however, awareness of the disease is increasing, and best practices to identify it are being proposed. The approach to suspected cases of ATTR-CM relies on the presence of heart failure, red flag signs and symptoms, and age >65 or >70 for men and women respectively. Little is known about cases when it presents in early ages. Case: We report a 62-year-old African American male with past medical history of hyperlipidemia, prostate cancer, hypertension, bilateral carpal tunnel surgery that had debuted with a cardiac arrhythmia at age 55 and was diagnosed with heart failure several years later. Restrictive cardiomyopathy was suspected, and genetic screening was sent for ATTRm which confirmed a pathogenic trasnthyretin gene mutation. Endomyocardial biopsy was performed which confirmed cardiac amyloid deposition. Discussion: ATTR-CM is a rare disease with an increasing prevalence. Cases with out of proportion signs and symptoms of heart failure with preserved ejection fractions should raise the suspicion of ATTR-CM despite age.